Structural adjustment and economic revolution in Nigeria - Odife, Dennis O. (Ibadan : Heinemann Educational Books (Nigeria) Ltd., 1989)
This book is about the transformation of the Nigerian economy from one dependent on agriculture to one heavily dependent on oil.
Includes index.
Includes bibliographical references: p. 239-243.
oo 16/10/2018, ijb 07/02/2019
Loans
Keywords: Economic stabilization; Nigeria